Inorganic contaminants and radionuclides - Naidu, R. (Elsevier, 2023)
Inorganic Contaminants and Radionuclides is a single reference covering common inorganic contaminants in detail, including their distribution in the environment, challenges linked to management, geogenic sources, anthropogenic sources, exposure and effects, international agreements and legislation relating to the contaminant, remediation options and global case studies. In addition, the book provides summaries of contaminated sites and key details about contaminants to present a more comprehensive understanding and improve remediation and management practices. The book's clear, consistent organization makes it a valuable resource for researchers, students and practitioners working in environmental science, environmental management and environmental engineering. One of the major constraints to assessing and remediating contaminated sites is the lack of awareness of the extent and severity of contaminated sites amongst the community, regulators, policymakers, industry operators, university graduates and environmental managers. This book helps to manage these constraints.